An Analysis of Students’ Difficulties in Mastering Phrasal Verbs - Baiq Suprapti Handini; Muhammad Husnu; Marzuki Marzuki (Ahmad Dahlan Journal of English Studies, 2021)
This research aimed at knowing about an analysis of student’s difficulties in mastering phrasal verb. This research is descriptive qualitative research. The subject of research was the students of Hamzanwadi University which consisted of 10 students. In this research, observation, questionnaire, and semi structured interview, were used for collecting data. The researcher conducted a descriptive design to analyzed and understanding people or human problems and describe the situation which is related to the students’ problem when using phrasal verb. The finding revealed that the student’s in Hamzanwadi University get difficulties in mastering phrasal verb. Otherwise, based on the result of observation, questionnaire, and interview, were clarified that students in Hamzanwadi University faced many problems, such as lack of vocabulary, less understanding of phrasal verb and difficulty to produce sentences with phrasal verbs.